24.5k views
0 votes
E - 2f = -10
8e + 4f = 0

2 Answers

5 votes

Answer:

e=-2, f=4. (-2, 4).

Explanation:

e-2f=-10

8e+4f=0

-------------

e=-10+2f

e=2f-10

8(2f-10)+4f=0

16f-80+4f=0

20f=0+80

20f=80

f=80/20

f=4

e-2(4)=-10

e-8=-10

e=-10+8

e=-2

User Ipj
by
5.4k points
3 votes

Answer:

f = 4 e = -2

Explanation:

e - 2f = -10

8e + 4f = 0

Solve by substitution

8e + 4f = 0

8e = -4f

e = -0.5f

Substitute into e - 2f = -10

-0.5f - 2f = -10

-2.5f = -10

2.5f = 10

f = 4

Substitute into 8e + 4f = 0

8e + 16 = 0

8e = -16

e = -2

User Kahou
by
5.5k points